Factors associated with quality of life of chronic spontaneous urticaria patients in a Vietnamese population - Nguyen Thi Tra My; Le Huyen My; Vu Nguyet Minh; Nguyen Thi Ha Vinh; Mai Ba Hoang Anh; Doanh Le Huu (PLoS ONE, 2025)
Objective Chronic spontaneous urticaria (CSU) is a challenging condition that significantly impacts the affected patients. This study aimed to evaluate the quality of life (QoL) among patients with CSU in Vietnam and identify factors associated with QoL. Methods A cross-sectional study was conducted at the Vietnam National Dermatology and Venereology Hospital from June 2023 to March 2024. A total of 358 CSU patients aged 16 years or older were recruited. Data were collected using a structured questionnaire covering demographic, clinical, and laboratory characteristics. The Chronic Urticaria Quality of Life Questionnaire (CU-Q2oL) and the Weekly Urticaria Activity Score (UAS7) were utilized to assess QoL and disease severity. Multivariate Tobit regression models were performed. Results The CU-Q2oL total score had a mean of 48.67 (SD = 16.90) and a median of 46 (IQR = 35–59). The scores for individual CU-QoL subscales were as follows: pruritus (5.42±2.02), swelling (2.86±1.54), life activities (13.89±6.00), sleep problems (11.12±4.96), limits (6.52±2.66), and looks (8.85±4.09). Higher UAS7 scores were associated with lower QoL, and angioedema in the eyes and lips were associated with increased swelling domain and poorer overall QoL. Longer disease duration was associated with higher pruritus scores, while a history of allergy was related to poorer total QoL, sleep, and looks. Severe itching further degraded sleep quality. Positive Autologous Serum Skin Test (ASST) was correlated with lower overall QoL, particularly in swelling and limits domains. Positive Basophil Histamine Release Assay (BHRA) status was linked to poorer sleep quality domain. Conclusion CSU significantly impairs the QoL of patients, affecting physical, emotional, and social dimensions. Regular QoL assessments should be integrated into clinical practice to ensure comprehensive and patient-centered treatment strategies.